Experimental investigation on microlayer behavior and bubble growth based on laser interferometric method - Wang, Ji; Wang, Hongbin; Xiong, Jinbiao (Frontiers in Energy Research, 2023)
High-speed laser interferometry is synchronized with high-speed camera to visualize the dynamic microlayer behavior during bubble growth in pool boiling under pressures from 0.1MPa to 0.3 MPa. An Indium–Tin-Oxide (ITO) film coated on sapphire is employed as the heating unit to provide the nominal surface heat fluxes in the range from 90 to 150kW/m2. Based on the instantaneous microlayer thickness and photographed bubble images, microlayer formation and depletion and its relation with bubble growth is analyzed. Appreciable effects of pressure on microlayer dynamics and bubble growth have been observed. At higher pressure, the microlayer existence time decreases and consequently, the contribution of microlayer evaporation becomes less important. At elevated pressure, effects of liquid subcooling and surface heat flux on bubble growth become more pronounced. The dimensionless instantaneous maximum microlayer thickness, δ_max⁄√νt , shows exponential dependence on the ratio rd⁄r(b,1) which increases linearly with time before microlayer depletion. A correlation is proposed to predict the instantaneous maximum microlayer thickness synthesizing the two relations. The local heat flux will be overestimated and the wall temperature profile is contrary to the experimental observation when the flow inside the microlayer is negligible. During the bubble growth period, only part of the microlayer is evaporated and the internal flow inside cannot be neglected.